Evaluation of oral pentoxifylline in the management of oral submucous fibrosis - An ultrasonographic study - Jayachandran Sadaksharam; Sureshkumar Mahalingam (Wolters Kluwer Medknow Publications, 2017)
Aim and Objective: To evaluate the therapeutic efficacy of oral pentoxifylline in the treatment of oral submucous fibrosis (OSMF) patients by assessing the clinical symptoms such as burning sensation, mouth opening, and submucosal layer thickness and echogenicity using ultrasonography, both pre- and post-operatively. Materials and Methods: Thirty study subjects were included in the study and divided into two groups in single-blind randomized manner, oral pentoxifylline and dexamethasone group. Burning sensation, mouth opening, ultrasonographic submucosal thickness, and echogenicity were recorded both pre- and post-operatively. Any adverse effects reported by the patients were also noted. The data collected were statistically analyzed, and response to pentoxifylline and intralesional dexamethasone with hyaluronidase was observed using ultrasonography. Results: A highly significant reduction (P < 0.001) in burning sensation, improvement in mouth opening, and changes in submucosal thickness were noticed in both groups, and significant improvement (P < 0.05) in echogenicity in both the groups was noticed. However, pentoxifylline group showed marginally better improvement than dexamethasone group. Conclusion: Pentoxifylline can bring about significant improvement in OSMF, which can be used as better alternative where intralesional steroid was contraindicated or not well tolerated.